Comparative molecular prevalence and subtypes distribution of Blastocystis sp. a potentially zoonotic infection isolated from symptomatic and asymptomatic patients in Iran: A systematic review and meta-analysis - Asghari, Ali; Hassanipour, Soheil; Hatam, Gholamreza (Acta parasitologica, 2021)
Purpose The present systematic review and meta-analysis was aimed to assess the weighted molecular prevalence of Blastocystis sp . in humans along with the comparative molecular prevalence and subtypes distribution of Blastocystis isolated from symptomatic and asymptomatic patients in Iran. Methods International electronic databases including Medline/PubMed, ProQuest, Scopus, Embase, and Google Scholar were explored until 4th October 2020. Heterogeneity index was evaluated among studies using Cochran’s Q test and I 2 index. Finally, 23 eligible studies were qualified to be included in this review. Results The pooled molecular prevalence of Blastocystis sp. in Iran was reported 15.2% (95% CI 11.5–19.7). In addition, the molecular prevalence based on PCR-sequencing and STS primers was reported 12.5% (95% CI 8.6–17.7) and 19.8% (95% CI 13.1–28.8), respectively. Interestingly, there was a considerably higher prevalence among asymptomatic patients [25.1% (95% CI 20.8–30.0)] in comparison to symptomatic ones [21.0% (95% CI 15.9–27.2)]. In addition, the frequency of Blastocystis ST1, ST2, and ST3 from positive samples in symptomatic patients was 19.7%, 35.1%, and 47.4%, respectively. In addition, the prevalence of Blastocystis ST1, ST2, and ST3 from positive samples in asymptomatic patients was 27.1%, 26.8%, and 37.8%, respectively. The results obtained in Iran showed that Blastocystis is more common in asymptomatic patients compared to patients having clinical symptoms. Of note, ST3, as the most common subtype causing clinical symptoms, was the most prevalent reported subtype among both symptomatic and asymptomatic patients in the country. Conclusions Hence, the pathogenicity of the Blastocystis parasite is not subtype-specific and appears to be related to a variety of risk factors. Still the Blastocystis epidemiology is open to question and more large-scale studies should be performed on this aspect.